PENGARUH KEMUDAHAN PENGGUNAAN DAN KEPERCAYAAN TERHADAP KEPUASAN KONSUMEN DAN MINAT BELI ULANG KONSUMEN E-COMMERCE SHOPEE DI KOTA PEKANBARU - Wulangi Wilang; Jushermi Jushermi; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of ease of Use and trust onconsumer satisfaction and buying interest in e-Commerce Shopee in Pekanbaru.The population in this study is all consumers who have shopped online on ecommerce Shopee in Pekanbaru city whose number is unknown. Samplingtechnique used is non probability sampling with purposive sampling method. Thisstudy used primary data by distributing questionnaires to 105 respondents andthen the data was processed using Sructural Equation modeling analysis methodwith the help of warppls version 6.0 software. The results showed that: (1) ease ofuse had a positive and significant effect. on consumer satisfaction (2) trust has apositive and significant effect on consumer satisfaction (3) ease of use has apositive and significant effect on repurchase interest (4) trust has a positive andsignificant effect on repurchase interest (5) consumer satisfaction has a positiveand significant effect on interest repurchase (6) ease of use has a positive andsignificant effect on repurchase intention by mediating consumer satisfaction (7)trust has a positive and significant effect on repurchase interest by mediatingconsumer satisfaction. Keywords : Ease of Use, Trust, Consumer Satisfaction, Consumer RepurchaseInterest.